Fylogeografické zhodnocení hraboše východoevropské s ohledem k východokazašskému výskytu - Volfová, Tereza (Jihočeská univerzita, 2019)
The Eastern European vole (Microtus mystacinus) is an arvicoline rodent distributed across northern and eastern Europe, the Balkans, Turkey, Armenia, NW and N Iran, Russia as far east as the Tobol River in W Siberia, and W and N Kazakhstan. We present a novel records from eastern Kazakhstan (the village of Dzhambul - 49 14 21.3N, 86 18 29.9E and the village of Sekisovka - 50 21 9.18N, 82 35 46.5E) based on mtDNA and we discuss implications of this findings on biogeography of eastern Kazakhstanpopulations. Marine Isotope Stage 11 is considered an important period for the diversification of the arvalis species group. In the context of our study, it is important to analyse genetically discontinuous Siberian populations, and the current distribution of M. mystacinus in new localities in eastern Kazakhstan.
New record of Microtus mystacinus in eastern Kazakhstan: phylogeographical considerations
Keywords: Microtus mystacinus; Kazakhstan